An Illustration of SARS‐CoV‐2 Dissemination Within a Skilled Nursing Facility Using Heat Maps - Blackman, Carolyn (J Am Geriatr Soc, 2020)
OBJECTIVES: To illustrate dissemination and asymptomatic transmission of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) during a skilled nursing facility (SNF) outbreak. DESIGN: Case report. SETTING AND PARTICIPANTS: Residents of a 150‐bed SNF. MEASUREMENTS: Heat maps generated by the SNF's infection prevention team to track staff and resident symptoms and SARS‐CoV‐2 test results to identify infection patterns. RESULTS: The SNF experienced a severe outbreak of SARS‐CoV‐2 early in the pandemic. The initial cluster of residents with symptoms and the first confirmed case occurred on the SNF's dementia care unit. The insufficient availability and prolonged turnaround time of testing for both residents and staff at the outset of the outbreak prevented timely and accurate identification and cohorting of cases. Despite extensive other infection control measures being in place, SARS‐CoV‐2 disseminated widely through the facility within 3 weeks of the first confirmed case, resulting in significant morbidity and mortality. CONCLUSION: Early, rapid, universal SARS‐CoV‐2 testing of both SNF residents and staff at the outset of an outbreak and then repeatedly thereafter is critical to mitigate viral transmission. This will become even more important as states relax stay‐at‐home orders and SNF staff intermingle with communities that are increasingly mobile. Increased testing will inevitably result in more staff testing positive and having to self‐quarantine at home, meaning that states must partner with SNFs and other long‐term care providers to coordinate and support strategic staffing reserves that can supplement current frontline staff. J Am Geriatr Soc 68:2174–2178, 2020.